2016
DOI: 10.1002/jbio.201500282
|View full text |Cite
|
Sign up to set email alerts
|

High‐content cell death imaging using quantum dot‐based TIRF microscopy for the determination of anticancer activity against breast cancer stem cell

Abstract: We report a two color monitoring of drug-induced cell deaths using total internal reflection fluorescence (TIRF) as a novel method to determine anticancer activity. Instead of cancer cells, breast cancer stem cells (CSCs) were directly tested in the present assay to determine the effective concentration (EC ) values of camptothecin and cisplatin. Phosphatidylserine and HMGB1 protein were concurrently detected to observe apoptotic and necrotic cell death induced by anticancer drugs using quantum dot (Qdot)-anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Recent studies have indicated that existing CSCs in solid tumors lead to chemotherapy resistance; therefore, CSCs should be eliminated to overcome drug resistance [15]. CSCs are a limited subpopulation with specific properties like self-renewal that are detected in several malignancies such as melanoma, breast, prostate and colon [16,17]. Several studies have focused on isolating CSCs according to surface markers in order to develop new anticancer agents for targeted chemotherapy [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that existing CSCs in solid tumors lead to chemotherapy resistance; therefore, CSCs should be eliminated to overcome drug resistance [15]. CSCs are a limited subpopulation with specific properties like self-renewal that are detected in several malignancies such as melanoma, breast, prostate and colon [16,17]. Several studies have focused on isolating CSCs according to surface markers in order to develop new anticancer agents for targeted chemotherapy [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in delivery systems using quantum dots highlight their potential in nanomedicine, with modifications that enhance biocompatibility and efficacy [44,45,[52][53][54][55]. In targeted and co-delivery systems, quantum dots play a crucial role in advanced therapy, merging with biomolecules for precise therapeutic delivery, marking significant progress in medical nanotechnology [2,3,12,18,19,[21][22][23]56,57].…”
Section: Quantum Dot Products For Breast Cancermentioning
confidence: 99%
“…Quantum dot-based total internal reflection fluorescence (TIRF) microscopy was utilized to monitor drug-induced cell death in breast cancer stem cells, focusing on the detection of phosphatidylserine and HMGB1 protein to differentiate between apoptotic and necrotic cell death. This technique allowed for the precise determination of drug concentrations effective against breast cancer stem cells, providing valuable insights into their susceptibility to treatment [23]. A formulation for a targeted and pH-sensitive niosomal system (pHSN) was developed, incorporating quantum dot (QD)-labeled Trastuzumab (Trz) molecules.…”
Section: Quantum Dot-facilitated Cell Death Monitoring and Gene Deliv...mentioning
confidence: 99%
See 2 more Smart Citations